2018
DOI: 10.4081/ecj.2017.7036
|View full text |Cite
|
Sign up to set email alerts
|

Current application of high flow oxygen nasal cannula in acute hypoxemic respiratory failure in the emergency department

Abstract: High flow oxygen with nasal cannula (HFONC) is a relatively new mode of oxygen delivery. Advantages of HFONC versus conventional oxygen therapy (COT) encompass carbon dioxide washout, generation of a slight positive end-expiratory pressure and maintenance of humidified gas flow through airways. These features are mostly shared with non-invasive mechanical ventilation (NIMV), although with lack of a clearly comparable efficacy. In the last few years, HFONC has gained interest as a third alternative to COT and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…According to our daily experience we can speculate that the ideal PEEP is between 8 to 12 cmH 2 O in order to optimize alveolar recruitment and to increase functional residual capacity. 7,20 In addition to PEEP, ventilatory support through Pressure Support (PS) can increase lung volumes, prevent atelectatic/consolidated units and can be applied when venous admixture exceed 30%. These physiological assumptions, at the basis of our study, are well shown by previous results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our daily experience we can speculate that the ideal PEEP is between 8 to 12 cmH 2 O in order to optimize alveolar recruitment and to increase functional residual capacity. 7,20 In addition to PEEP, ventilatory support through Pressure Support (PS) can increase lung volumes, prevent atelectatic/consolidated units and can be applied when venous admixture exceed 30%. These physiological assumptions, at the basis of our study, are well shown by previous results.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] HFNC has been developed initially for critically ill neonate and infantes, 4,5 however, in the last decade evidence suggested it is effective in diverse underlying conditions, such as hypoxemic respiratory failure, pre and post intubation, exacerbation of Chronic Obstructive Pulmonary Disease (COPD), sleep apnea, acute heart failure, and conditions entailing do-not-intubate orders. [6][7][8] HFNC could alleviate symptoms of acute respiratory failure with different mechanisms: deadspace CO 2 washout, reduction of oxygen dilution (ensuring a more precise fraction of inspired oxygen, FiO 2 ) and produce a moderate positive airway pressure effect when mouth is closed. 9,10 Finally they seem to be very tolerable and comfortable 3 due to the heated and humidified inspired gases.…”
Section: Introductionmentioning
confidence: 99%